AI-driven strategies for advancing corneal cell therapy: a promising frontier - Tafti, Mahsa Fallah; Khorrami-Nejad, Masoud; Arabfard, Masoud; Ghiasi, Mohsen; Afkhamizadeh, Fatemeh; Jadidi, Khosrow; Aghamollaei, Hossein (Frontiers in Medicine, 2025)
Cell-based therapies offer an alternative to corneal transplantation for the management of corneal diseases. However, these approaches require a deeper understanding of the principles of cell therapy, and the ability to predict and diagnose outcomes pre- and post-operatively is highly desirable. Recently, the development of innovative techniques that leverage predefined data from multiple cohorts with corneal diseases has received considerable attention. Approaches using artificial intelligence (AI) can address major concerns in corneal cell therapy, including the identification of novel biomarkers, improvements in cell delivery processes, and the acceleration of personalized treatments. This review summarizes real-world examples of AI applications from preclinical through clinical studies, with a focus on corneal cell-based therapies.